Behavioural Risk Factors, Hypertension Knowledge, and Hypertension in Rural India - Eslavath Rajkumar; John Romate (International Journal of Hypertension)
Hypertension is an important health problem in India. The emergence of hypertension and other cardiovascular diseases are strongly related to various risk factors. Knowledge about hypertension and related risk factors is often stressed on their utility in prevention and management of the disease. Still, there is a poor understanding about associated behavioural risk factors of hypertension and importance of knowledge in adopting health-promoting behaviours and controlling hypertension among rural areas of India. This study aimed at assessing the association of behavioural risk factors with hypertension knowledge and hypertension among rural population. The present study focused on a south-western state of India from which a taluk with one of the lowest socioeconomic ratings was selected. A total of 263 participants were selected by using a multistage random sampling technique. Data were collected by in-person interview using behavioural risk factors questionnaire, hypertension knowledge questionnaire, and physical measurement. Data were analysed using descriptive statistics, chi square, Pearson correlation and binary logistic regression. Findings revealed that there is no significant relationship between risk factors index and knowledge of hypertension. It was also observed that factors such as smoking (OR = 0.29; CI: 090–0.961), fruit and vegetable consumption (OR = 1.32; CI: 1.01–1.74), body mass index (OR = 1.85; CI: 1.21–2.84), and age group (OR = 1.55; CI: 1.14–2.11) were significantly associated with the odds of hypertension. The factors such as smokeless tobacco use, alcohol consumption, physical activity, gender, education, and occupation were not associated with the odds of hypertension. Future research should focus on bringing down the associated risk factors to prevent and control hypertension.